Institutions and information flows, and their effect on capital flows - (:unkn) unknown (ELSEVIER SCIENCE BV, 2018)
We examine the empirical role of information flows and institutional quality in explaining the capital flows per capita across countries, and their role in explaining the so-called Lucas paradox-low levels of capital flows to poor countries. The findings of this paper suggest that countries with better institutions and high information flows receive high capital flows, and information flows also provides a partial explanation to the Lucas Paradox. The latter result is significant even after controlling for institutional quality, financial openness and human capital differences across countries, and using instrumental variable for information flows. This paper also examines the indirect effects of institutional quality on capital flows per capita through its impact on information flows and finds that countries with better institutional quality have higher levels of information flow. Accounting this indirect effect is economically important and papers that do not account for this indirect effect of institutions on capital flows per capita would underestimate the effect of institutions on capital flows per capita. Findings of this paper suggest that relatively poorer countries should improve their institutional quality and increase their access to worldwide information and promote investments in communications infrastructure to attract long-term capital flows. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Capital flows; Information flows; Lucas Paradox; Institutional quality; Telecommunications; COLONIAL ORIGINS; ECONOMIC-GROWTH; INFRASTRUCTURE; GLOBALIZATION; GEOGRAPHY; TRANSACTIONS; DETERMINANTS; RICH